START—the Swiss tele-assisted rehabilitation and training program to support transition from inpatient to outpatient care in the subacute phase after a stroke: feasibility, safety and performance evaluation - Gäumann, Szabina; Ziller, Carina; Paulissen, Nele; Behrendt, Frank; Suica, Zorica; Crüts, Björn; Gammerschlag, Luana; Parmar, Katrin; Gerth, Hans Ulrich; Bonati, Leo H.; Schuster-Amft, Corina (Frontiers in Digital Health, 2025)
IntroductionEffective rehabilitation is essential to prevent physical and cognitive decline, but many stroke patients face challenges to maintain rehabilitation efforts after hospital discharge. Telerehabilitation, delivered via digital platforms, represents a promising approach for intensive continuation of stroke rehabilitation after discharge. The Swiss tele-assisted rehabilitation and training program (START), delivered through the Blended Clinic mobile application, seeks to support patients to start during inpatient rehabilitation, continue during the transition to the home environment, continue until outpatient rehabilitation starts and beyond. The study aims to evaluate feasibility, safety and performance of the START program on the Blended Clinic platform during inpatient, transition, and outpatient rehabilitation with patients in the early and late subacute phase after a stroke. Furthermore, patients' functional status, mobility and activity level, and health-related quality of life are monitored.MethodsThis single-center feasibility trial with three measurement sessions will include 40 patients, who will be introduced to START during their inpatient rehabilitation. Patients will continue for 12 weeks post-discharge. For the feasibility assessment, process-, training- and mHealth-related parameter will be evaluated, which include recruitment rate, process-evaluation, safety, adherence, drop-out rate, stability and maintenance of the system, usability, quality, satisfaction, user and program experience, and perceived change. Secondary outcomes will focus on motor function, mobility, quality of life, activity level, heart rate, blood pressure, and performance-based measures.DiscussionThe study's strengths include its foundation in previous usability analyses, which informed refinements to the START program. The study's design is based on the ISO 14155 standard, ensuring high standards for medical device research and supporting the future certification of the START program on the Blended Clinic platform. Potential challenges include patient self-reporting via the mobile application and barriers related to technology use among older adults and older mobile devices. Additionally, the availability of coaching is limited to business hours, which may affect adherence. Despite these challenges, the study's findings will provide insights into the feasibility of mobile-based telerehabilitation and guide the design of a future randomized controlled trial. Clinical Trial RegistrationThe study is registered with the Swiss National Clinical Trial Portal (SNCTP000005943), EUDAMED (CIV-CH-24-05-046954), and clinicaltrils.gov (NCT06449612).